Project-Based Learning with Examples Non-Examples to Improve Digital Literacy through Short Movie Ads - Erinda, Hayyu; Karina, Anggita Ajeng; Wijaya, Dandi Nurmansyah; Nikma, Irfianninza Risquillia; Yuliono, Gun; Ulum, Miftahul; Widayanti, Erma; Christianto, Yudhi (Letters in Information Technology Education (LITE), 2024)
This study explores the effectiveness of the Project-Based Learning (PjBL) method combined with the Examples Non-Examples approach in enhancing students' digital literacy outcomes through the production of short movie advertisements. In an increasingly digital era, digital literacy has become an essential skill that students must master. PjBL offers a learning approach that actively engages students in real-world projects, while the Examples Non-Examples method provides concrete guidance through both positive and negative examples. This study employs the Classroom Action Research (CAR) model using Kurt Lewin's cycle, involving 36 students from class X.7 at SMAN 8 Malang. Data were collected through observation and documentation studies and analyzed descriptively, both qualitatively and quantitatively. The results indicate that the application of this method significantly improves students' understanding and skills in digital literacy, particularly in video editing, visual composition, and creativity. The study concludes that PjBL with the Examples Non-Examples approach is effective in enhancing students' digital skills and soft skills, and it offers a meaningful contribution to the development of digital learning methods.